2018
DOI: 10.1039/c8nr04407d
|View full text |Cite
|
Sign up to set email alerts
|

Reversible resistive switching behaviour in CVD grown, large area MoOx

Abstract: Non-volatile resistive memory devices are theorized to be the most promising pathway towards analog memory and neuromorphic computing. Two-dimensional MoO3 is a versatile planar transition metal oxide, whose properties can be readily tuned, making it anywhere from a wide bandgap semiconductor to a semi-metal. Successful integration of such a planar metal oxide into resistive memory can enable adaptive and low power memory applications. Here, we investigate the non-volatile and reversible resistive switching be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…We tested the behaviour of three devices for different sizes 40×40 μm 2 , 20×20 μm 2 , 10×10 µm 2 as shown in the Figure S1. We observed similar behaviour as 60×60 μm 2 . We can see slight variation from size to size, but overall there was negligible deviation with respect to switching type, switching direction, and switching voltages.…”
Section: Effect Of Device Size On the Switching Behavioursupporting
confidence: 84%
“…We tested the behaviour of three devices for different sizes 40×40 μm 2 , 20×20 μm 2 , 10×10 µm 2 as shown in the Figure S1. We observed similar behaviour as 60×60 μm 2 . We can see slight variation from size to size, but overall there was negligible deviation with respect to switching type, switching direction, and switching voltages.…”
Section: Effect Of Device Size On the Switching Behavioursupporting
confidence: 84%
“…As a result, a surface MoO monolayer will be formed, which serves as the active catalytic substrate for ORR and OER, that is also observed in our XPS, XRD, and STEM characterization experiments (Figure 4a–d; Figures S17 and S18, Sections S9 and S11, Supporting Information). [ 66,67 ] To further confirm the existence of oxide layer, we have performed ultraviolet photoelectron spectroscopy (UPS) experiments of the cathode after the first charging process (Section S16, Supporting Information). Our measurements (Figure S29, Supporting Information) indicate 0.25 eV lower work function for the oxidized Mo 3 P (3.18 eV) compared with pristine Mo 3 P (3.43 eV) further supporting the existence of the oxide overlayer on Mo 3 P that can be a reason for high activity of this catalyst for both ORR and OER.…”
Section: Figurementioning
confidence: 99%
“…No preferential orientation for the MoO 3– x layer exists, and minimal interfacial MoO x oxide is present possibly due to the effects of rapid heating and cooling PVD process. [ 36,39 ] The Raman spectra of bare GaN NRAs and GaN/MoO 3– x NRAs heterojunctions show the same Raman peak position and intensity in 564.4 cm −1 corresponding to the GaN E 2 (high) phonon mode (Figure 2d). [ 40 ] This observation indicates the good quality and stability of GaN NRAs after MoO 3– x layer deposition.…”
Section: Resultsmentioning
confidence: 98%
“…Many studies have reported that α‐MoO 3 can be easily reduced to form MoO 3– x by high‐temperature/vacuum environment or a reducing atmosphere. [ 35,39,44–46 ] In the present work, we used PVD thermal evaporation with a growth temperature of 800 °C to obtain MoO 3– x . Previous works used similar experimental conditions of PVD have reported oxygen deficiencies of MoO 3– x .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation